Multiaxial low-cycle-fatigue of stainless steel 410 alloy under proportional and non-proportional loading. (August 2021) - Albinmousa, Jafar; Adinoyi, Muhammed J.; Merah, Nesar
Abstract: Stainless steels are known for their high corrosion resistance and strength to be used for load-bearing components. While the fatigue behavior of common stainless steel grades such as 304 and 316 are thoroughly investigated, research on multiaxial fatigue of AISI 410 is lacking. In-phase and 90° out-of-phase multiaxial fatigue loading tests were performed on AISI 410 specimens under strain-controlled conditions. Like other stainless steel grades, additional stress hardening of the alloy was observed under non-proportional loading. The evolution of equivalent stress amplitude with cycling shows that the material exhibits cyclic stress softening. In general, the fatigue damage model of Fatemi-Socie was found to overestimate the multiaxial fatigue lives of SS 410, particularly, for 90 ° out-of-phase loading path. Itoh's non-proportional strain range was also found to overestimate multiaxial fatigue lives, however, it was found to provider better estimate for the 90° out-of-phase loading path. This observation suggests that Itoh's non-proportional factor f N F, plays an important role in the modeling of out-of-phase multiaxial fatigue behavior of SS 410 stainless steel. Highlights: Multiaxial in-phase and out-of-phase fatigue behavior of SS410 is investigated. Non-proportional cyclic hardening was observed in axial and shear modes. SS410 exhibits cyclic softening in axial and shear modes. Fatemi-Socie and Itoh models were examined.